Analisis Labelisasi Halal dalam Produk Makanan dan Minuman pada UMKM Kota Bengkulu - Fadillah Alfatihah; Asnaini; Eeng Juli Efrianto (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the implementation of halal labeling on food and beverage products among MSMEs in Bengkulu City, identify internal and external factors influencing business owners' decisions to obtain certification, and examine its impact on consumer trust and product competitiveness. This research employed a descriptive qualitative approach and field research methods through observation, interviews, and documentation. Informants consisted of seven MSME owners who had undergone the halal certification process. The findings reveal that most business owners have a good understanding of halal certification procedures, although technical assistance is still needed. Internal factors such as capital readiness, commitment, and awareness, along with external factors including market trends and consumer demand, influence decision-making regarding halal certification. The implementation of halal labeling has shown a positive impact by increasing consumer confidence, strengthening product competitiveness, and enhancing market opportunities.